Exploring weight bias and negative self-evaluation in patients with mood disorders: insights from the BodyTalk Project - Meneguzzo, Paolo; Behrens, Simone C.; Pavan, Chiara; Toffanin, Tommaso; Quiros-Ramirez, M. Alejandra; Black, Michael J.; Giel, Katrin E.; Tenconi, Elena; Favaro, Angela (Frontiers in Psychiatry, 2024)
All participants, who were adults, gave their informed consent before engaging in the study. The research adhered to the ethical principles of the Declaration of Helsinki and received approval from the Padova Ethics Committees for Clinical Practice.PM, SCB, CP, TT, MAQR, BM, MJB, KEG, ET, AF designed the study and wrote the protocol. SCB, MAQR, and MB managed the development of the tasks. PM and SCB undertook the statistical analysis, and PM wrote the first draft of the manuscript. All authors contributed to the revision and have approved the final manuscript.